2020
DOI: 10.1007/s12144-020-01220-2
|View full text |Cite
|
Sign up to set email alerts
|

A diary study of impulsive buying during the COVID-19 pandemic

Abstract: The purpose of this paper is to explore why impulsive buying happens under emergency and crisis situations, such as that of COVID-19. Drawing on the cognitive-affective personality system theory (CAPS), we tested the dynamic influence of daily perceived uncertainty on COVID-19 on daily impulsive buying via daily information overload and daily information anxiety in a two-wave experience sampling method (ESM) design. Through a multilevel structural equation model (MSEM) analysis, we found that the daily perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 88 publications
2
46
0
Order By: Relevance
“…In terms of our rst aim, we found a gradually increasing trend of compulsive buying patterns during an extended period of the Covid-19 pandemic from our sample. Although there was an indication that compulsive buying increased after the outbreak of pandemic compared to before Xiao et al, 2020), the gradual increase of compulsive buying over an extended period during the course of pandemic has never been reported before. On the other hand, we also found that the increase in compulsive buying pattern was signi cant only in the low-SES and low-income groups both in the online and in the o ine context.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In terms of our rst aim, we found a gradually increasing trend of compulsive buying patterns during an extended period of the Covid-19 pandemic from our sample. Although there was an indication that compulsive buying increased after the outbreak of pandemic compared to before Xiao et al, 2020), the gradual increase of compulsive buying over an extended period during the course of pandemic has never been reported before. On the other hand, we also found that the increase in compulsive buying pattern was signi cant only in the low-SES and low-income groups both in the online and in the o ine context.…”
Section: Discussionmentioning
confidence: 82%
“…There is evidence, that compulsive buying also increased during the Covid-19 pandemic (Çelik & Köse, 2021;Islam et al, 2021;, however, authors typically report retrospective data collection or two-point comparison of CB behaviour in the sample. The only study which collected data regarding CB covered an extended period of seven days at the end of February 2020 in China used experience sampling in 150 individuals and concluded that perceived uncertainty in uenced (and information overload and anxiety about Covid-19 mediated) daily impulsive buying behaviour (Xiao, Zhang, & Zhang, 2020). However, not only internal (such as coping style), but also external factors (such as the availability of nancial resources) in uence people's decision to buy.…”
Section: Introductionmentioning
confidence: 99%
“…It is seen that the findings obtained about the research are consistent with the consequences of the previous studies. When the findings obtained from the study are compared with the results of the study in the literature, the effect of perceived threat on anxiety by Song, Yao, and Wen (2021), Shahzad et al (2020), and Paredes et al (2021), the effect of anxiety on impulsive buying by Laato et al (2020), Xiao, Zhang, and Zhang (2020) studies and finally moderator effects are in parallel with Sheeran and Abraham (1996), Joshi and Rahman (2015), Laato et al (2020) studies.…”
Section: Discussing the Findings With The Literaturementioning
confidence: 88%
“…People's purchase behaviors during the COVID-19 outbreak in regard to masks, personal hygiene products and food revealed t significant changes in consumption patterns in the face of the dangers and uncertainly of the pandemic crisis. A list of studies identified such shopping behaviors as impulsive and stockpiling (Hall et al, 2020(Hall et al, , 2021Zhang et al, 2020;Ahmed et al, 2021;Arafat et al, 2021;Barnes et al, 2021;Wang et al, 2020;Harahap et al, 2021;Islam et al, 2021;Kaur and Sharma, 2020;Li et al, 2020;Naeem, 2020;Xiao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Social media placed additional pressure on people, increasing levels of fear and concern (Arafat et al, 2021;Hall et al, 2020;Barnes et al, 2021;Islam et al, 2021). Moreover, the high density of information on the COVID-19 situation coming from local authorities also contributed to stockpiling behaviors (Xiao et al, 2020). An analysis of the amount of transactions made in retail sectors between January 2017 and December 2020 shows an increase in spending during COVID-19 greater than is normally seen for Christmas and Black Friday (Hall et al, 2021).…”
Section: Introductionmentioning
confidence: 99%